Kiprah Lulusan Program Studi Manajemen Pendidikan Islam Pada Dunia Kerja Di Kalimantan Timur - Muhammad Iwan Abdi; Ananiah Ananiah (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2013)
This research was to measure the level of satisfaction users of Management Education Islam alumnus at public and privat sectors. Furthermore, the research is to mapping the types of professions and distribution of alumnus in East Kalimantan. The aims of this research are to know key position and to measure level of satisfaction of the carrier institutions that use alumnus of Management Education Islam at East Kalimantan. This research is qualitative descriptive with study case approach. Writer used observation, questionnaire and documentation to collect data. Analysis of data using percentage formula and mean test. The conclusions are: (1) Alumnus of Management Education Islam has key position at carrier world with professions: Administration Staff at College, Bank Teller, Customer Service at Bank, Administration at Finance and at Telkomsel, Imam KUA, and Board on Religius Organizations; (2) Distribution of alumnus: Samarinda, Balikpapan, Nunukan, Tarakan, Bulungan and Paser; (3) 59% alumnus has key position appropriate with their academic background and 41% not appropriate; and (4) Level of measurement of the user of the alumnus at 2,318. It is at range 1,668-2,334 that means satisfy. So we can say that alumnus of Management Education Islam in order to do their job is good enough.